Investigation of the effect of training attachment behaviors to pregnant mothers on some physical indicators of their infants from birth to three months based on the separation of male and female infants - Sara dokuhaki; Maryam Heidary; Marzieh Akbarzadeh (Elsevier, 2019)
Background: Maternal attachment to the fetus during pregnancy improves infant's growth and development and is an important criterion for public health. The aim is to investigate the effect of training attachment behaviors to pregnant women on some growth health indicators of infants. Methods: This is a clinical trial with convenience sampling which was conducted on 190 pregnant women in Hafez Hospital in Shiraz who randomly classified into intervention and control groups. For the intervention group, 6 sessions of 90-min classes were held. After delivery, both groups were compared in terms of physical growth (weight, height, head circumference) at birth, one and three months after birth. The data were analyzed using repeated Measurement. Results: Weight increase in female infants in the intervention group compared to the control group was significant at birth (p = 0.016), one month (p = 0.010) and three months after birth (p = 0.014). Height increase in female infants in the intervention group compared to the control group was significant at birth (p = 0.025), one month (p < 0.001) and three months after birth (p = 0.009). Male gender was not statistically significant in any age group but it increased the size of the head circumference of three-month-old infants. Conclusion: Training of attachment skills to mothers improves height and weight of female infants in three steps. The average index for boys in the intervention group was higher than that of control group, but it was not significant. Key Words: attachment, infant, weight